Clustered P2P based resource query and dissemination for multi-hop wireless mesh network - Ji-gang WEN; Kun XIE; Gao-gang XIE; Guang-xing ZHANG; Ren-fa LI (Tongxin xuebao)
According to the character of mesh topology and character of the different types of mesh nodes,the multi-hop wireless mesh network was modeled as clustered P2P.Moreover,in order to save the message bandwidth,the Bloom filter as the message to represent the resource list abstract was used,and the message was transmitted among the constructed P2P clusters.To minimize the downloading interruption due to mobility of clients,a resource-density-sensitive resource query and dissemination algorithm in which the query was transmitted to the cluster that had the maximum number of replica resources was proposed.The simulation results show that the proposed resource query and distribution algorithm can provide appealing resource downloading performance.